Antimicrobial activity of phenolic extract of apple pomace against Paenibacillus larvae and its toxicity on Apis mellifera - Giménez Martínez, Pablo Darian (2020)
Apis mellifera populations are exposed to different biotic and abiotic stressors that affect bee survival. Paenibacillus larvae, the causative agent of American foulbrood, is one of the most important bacterial pathogens that affect bee health. In some countries, the use of antibiotics is the most common method for the prevention and treatment of P. larvae infected colonies, however this application can also increase the risk of occurrence of resistant strains. An ecological alternative is the use of vegetal extracts containing bioactive compounds, such as polyphenols. The aim of this study is to check the antimicrobial activity of phenolic extracts of apple pomace, from the cider industry, against P. larvae strains by the broth micro dilution method. In addition, the toxicity of the phenolic extracts on A. mellifera was verified using the complete exposure method. All extracts contain from 715.31 to 11348.16 μg gal/g DW, determined by Folin-Ciocalteu show antimicrobial activity against P. larvae genotype ERIC I, ranging from 23 μg/mL to 150 μg/mL. Toxicity assays of apple pomace extracts on adult bees exhibited a maximum mortality of 18% after 48h. This promising alternative will be used in the future to evaluate its toxicity at a field level.